PWM Control of AC Chopper Fed by Unbalanced 3-Phase Voltage Source - Macit, Nurbanu; Sünter, Sedat (Fırat University, 2017)
In recent years, power electronic has become even more popular with the development of semiconductor switching devices. Power electronics applications can be found almost in all systems related to electrical and electronic fields. With the power electronic circuits, AC or DC voltages at various amplitudes can be obtained from constant voltage sources. AC voltage with constant frequency and variable amplitude with high power factor can be provided by an AC chopper. Purpose of these power electronic circuits is to make the system more efficient, provide output waveforms with higher quality (less harmonics) and prevent power loss in large power systems. In this study, a three-phase PWM controlled AC chopper circuit has been modelled and simulated in MATLAB / Simulink package program. In this simulation, the output statements obtained for the switching devices by a different control method are discussed. Various operating conditions have been examined where a three-phase unbalanced voltage source without and with having the 5th and 7th harmonics was applied to the input side of the chopper. As a result, superiority of the control system used in the PWM controlled AC chopper has been demonstrated by the simulation results.